Adherence of Family Caregivers of Patients with Stroke to Rehabilitation Regimen - Nahid Dehghan Nayeri (حیات, 2012)
Background & Objective: Due to physical and mental complications, stroke causes disability in self-care and adherence to rehabilitation in patients. The purpose of this study was to assess the adherence to rehabilitation regimen in family caregivers of patients with stroke.